2017
DOI: 10.1016/j.vaccine.2017.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel, protein-based pneumococcal vaccine against nasopharyngeal carriage of Streptococcus pneumoniae in infants: A phase 2, randomized, controlled, observer-blind study

Abstract: PATH, GlaxoSmithKline Biologicals SA. ClinicalTrials.gov identifier NCT01262872.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
1
56
0
3
Order By: Relevance
“…Another important implication of our work is that immune responses demonstrable in mouse models do not accurately predict those of humans. In light of the recent failure of at least two different protein vaccine formulations (33,34) to provide protection against colonization, one is left wondering whether excessive reliance on mouse models may be responsible. Clearly, murine models are much more convenient (25) a Shown are data for the top 50% of responders from ranked screen results for immunized mice (WCV), exposed mice (exposed), and human IL-17A (human).…”
Section: Figmentioning
confidence: 99%
“…Another important implication of our work is that immune responses demonstrable in mouse models do not accurately predict those of humans. In light of the recent failure of at least two different protein vaccine formulations (33,34) to provide protection against colonization, one is left wondering whether excessive reliance on mouse models may be responsible. Clearly, murine models are much more convenient (25) a Shown are data for the top 50% of responders from ranked screen results for immunized mice (WCV), exposed mice (exposed), and human IL-17A (human).…”
Section: Figmentioning
confidence: 99%
“…The relatively larger responses seen in blood than in adenoidal cells occur in the context of a much lower background cytokine production by unstimulated cultures and a known lower T regulatory environment, and has previously been observed by us and others [42,43]; however, further investigation is required to further understand this observed difference. Of particular note were the relative lack of responses to PhtD evident in blood, an antigen which has recently been shown to lack efficacy against pneumococcal colonization in children, although when injected parenterally with aluminium rather than a T cell adjuvant [44]. Although it has been proposed that this and related pneumococcal proteins, which are released extracellularly by the bacterium in large quantities, might act as a sink for potentially opsonophagocytosing antibodies [45], our data suggest that PhtD may also fail to induce cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro and in vivo assays have shown the bioactivities of many pneumococcal proteins, but adding them into vaccines requires assays that accurately correlate a functional assay with protection, often independent of prevention of sepsis. The difficulty of implementing this requirement was illustrated by a recent Phase II clinical trial of a combination of 10 polysaccharides with the histidine triad protein PhtD and a pneumolysin toxoid [12]. PhtD is believed to participate in zinc homeostasis in the nasopharynx, and the toxin pneumolysin causes damage to respiratory epithelial cells during pneumonia; both vaccine antigens decreased nasopharyngeal carriage in preclinical models [13,14].…”
Section: Multi-modal Protection: Protein Functions Enter the Vaccine mentioning
confidence: 99%
“…This is essentially an OPK assay, which is not expected to be highly relevant to nasopharyngeal carriage. One trial in Gambian infants reported that the proteins produced high titer antibodies but failed to decrease nasopharyngeal carriage of any pneumococci (serotypes within or outside those in the vaccine) [12]. The key question remains: Did this failure arise because the antigens failed to generate antibodies (quality and quantity) directed to mucosal events in disease?…”
Section: Multi-modal Protection: Protein Functions Enter the Vaccine mentioning
confidence: 99%